Багатоступеневий підхід РФ у побудові і розповсюдженні дезінформації: приклад “продажу зброї” - Осадчук, Роман Юрійович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The article investigates Russian influence operations aimed at discrediting Ukraine and undermining military support for Ukraine from allies. The author reviews and conceptualizes real-life influence operations conducted by Russia after the full-scale invasion of Ukraine in 2022 that promoted disinformation stories about Western-donated arms sales by Ukraine. Analyzing such campaigns is essential for understanding the current and future influence that such disinformation attempts might achieve. The article strives to conceptualize malign influence campaigns into a model that might serve as a template for analyzing further propaganda and disinformation campaigns.